Cardiopulmonary exercise testing in patients undergoing radical cystectomy (open, laparoscopic and robotic). (November 2014) - Hoyland, Kimberley; Vasdev, Nikhil; Adshead, James M; Thorpe, Andrew
The use of cardiopulmonary exercise testing (CPET) is gaining popularity as a preoperative functional assessment tool and is a useful adjunct to risk stratification before radical cystectomy. It is important for urologists to understand the indications, contraindications, methodology and different parameters evaluated during CPET assessment and use this information acquired to tailor pre-, intra- and postoperative care in patients undergoing a radical cystectomy. We present a review on the increasing role of CPET in patients undergoing a radical cystectomy.